Pest Identification Guide: Rugose Spiraling Whitefly, Aleurodicus rugioperculatus - Nicole A Casuso; Hugh A. Smith (EDIS, 2018)
Rugose spiraling whitefly (Aleurodicus rugioperculatus) feeds on over 118 hosts including coconut palm, gumbo limbo, and other fruits and ornamentals. It is a major pest in Florida. Learn to identify these tiny flies with this handy, 2-page guide written by Nicole A. Casuso and Hugh A. Smith and published by the UF/IFAS Entomology and Nematology Department. https://edis.ifas.ufl.edu/in1202